The effectiveness of supplemental instructional activities on eighth-grade students’ understanding of the system of equations unit in pre-algebra - Pursell, Elizabeth (Kansas State University, 2024)
Cognitive development of eighth-grade students, as identified by Jean Piaget, occurs during a time when many of them are transitioning between concrete operations and formal operations where the ability to think in abstract concepts becomes possible. Because of this period of transition, many eighth-grade students find difficulty in demonstrating their understanding of the abstract concepts presented in the systems of equations unit of pre-algebra. The purpose of this study was to investigate the effectiveness of supplemental instructional activities on eighth-grade students’ understanding of the systems of equation unit of pre-algebra. One hundred-ten middle school pre-algebra students in a rural Midwestern area of the United States provided data for a pretest-posttest control-group design. All participants received similar instruction on the systems of equations using an 11-day unit design. Students in the control group (n= 23) received no supplemental instructional activities, where students in the Experimental Group A (n= 45) received the same instruction, paired with supplemental instructional activities that utilized pencil and paper. A second experimental group, Experimental Group B (n= 42) experienced supplemental instructional activities that utilized technology. Using pre-test and post-test scores, results of an analysis of covariance (ANCOVA) revealed that a significant difference existed (P = 0.17) between students who received no supplemental instructional activities (Control Group) and students who experienced supplemental instructional activities (Experimental Group A & B). The researcher also wished to explore if a significant difference existed between the modality of the supplemental instructional activities. It was found that no significant difference existed (P = 0.813) between the students who experienced supplemental instructional activities involving pencil and paper and those who utilized technology. These results strongly advocate the need to provide supplemental instructional activities to eighth-grade students to aid the comprehension of the abstract nature that exists in the systems of equations unit of pre-algebra, and that the modality of these supplemental instructional activities may not be a factor in student comprehension and outcomes.
Keywords: Supplemental instructional activities; Pre-algebra; Systems of equations; Piaget; Concrete operations; Formal operations